The role of regulatory B cells in immune regulation and childhood allergic asthma - Caroline Vanessa Kliem; Bianca Schaub (Molecular and Cellular Pediatrics, 2024)
Abstract Background As the most common chronic disease in childhood, asthma displays a major public health problem worldwide with the incidence of those affected rising. As there is currently no cure for allergic asthma, it is mandatory to get a better understanding of the underlying molecular mechanism. Main body By producing IgE antibodies upon allergen contact, B cells play a pivotal role in allergic asthma. Besides that, IL-10-secreting B cell subsets, namely regulatory B cells (Bregs), are reported in mice and humans to play a role in allergic asthma. In humans, several Breg subsets with distinct phenotypic and functional properties are identified among B cells at different maturational and differentiation stages that exert anti-inflammatory functions by expressing several suppressor molecules. Emerging research has focused on the role of Bregs in allergic asthma as well as their role for future diagnostic and preventive strategies. Conclusion Knowledge about the exact function of human Bregs in allergic asthma is still very limited. This review aims to summarize the current knowledge on Bregs. We discuss different human Breg subsets, several ways of Breg induction as well as the mechanisms through which they exert immunoregulatory functions, and their role in (childhood) allergic asthma.